Pelatihan Penggunaan Alat Edukasi Kartu Bergambar (Flash Card) dalam Pembelajaran Matematika pada Siswa Madrasah Ibtidaiyah - Rani Rahim; Asrindah Nasution; Rizka Fahruza Siregar; Rini Ramadhani; Nova Riani; Winanda Marito (Educate: Journal of Community Service in Education, 2025)
Educational tools are very important to be implemented in the learning process. This is because educational tools can increase students' learning motivation so that learning is more meaningful, innovative and creative. However, the reality in the field is that when the learning process is in the classroom, teachers do not use learning media such as educational tools. This results in low student interest in learning mathematics, which also makes students' mathematical abilities low. Therefore, the community service team carried out community service activities regarding the use of educational tools in classroom learning. This community service activity aims to increase students' interest in learning and also their mathematical abilities. This community service activity was carried out at MIS Nurul Hidayah Medan. Participants in this activity were grade IV students consisting of 32 students. This activity was carried out on May 7, 2025. The methods used in this community service activity were preparation and planning, implementation and evaluation. The results of this community service activity were that students were more interested and enthusiastic in using educational tools with picture cards (flash cards) and there was an increase in students' mathematical abilities after using the educational tool.